2017
DOI: 10.1002/advs.201700200
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Quasi‐Omnidirectional Solar Cells with Superior Electrical Performance by All‐Solution‐Processed Si Nanopyramids

Abstract: Large‐scale (156 mm × 156 mm) quasi‐omnidirectional solar cells are successfully realized and featured by keeping high cell performance over broad incident angles (θ), via employing Si nanopyramids (SiNPs) as surface texture. SiNPs are produced by the proposed metal‐assisted alkaline etching method, which is an all‐solution‐processed method and highly simple together with cost‐effective. Interestingly, compared to the conventional Si micropyramids (SiMPs)‐textured solar cells, the SiNPs‐textured solar cells po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
(24 reference statements)
1
29
0
Order By: Relevance
“…Such diffuse reflections could be reduced by generating subwavelength nanostructures. 43,44 In the present work, since the surface roughness of the nanostructures is smaller than the visible light, they inhibit undesirable light reflections and scattering. Optical Modeling of Double-Sided γ-AlOOH AR Coating.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Such diffuse reflections could be reduced by generating subwavelength nanostructures. 43,44 In the present work, since the surface roughness of the nanostructures is smaller than the visible light, they inhibit undesirable light reflections and scattering. Optical Modeling of Double-Sided γ-AlOOH AR Coating.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The introduction of the pre‐patterned micro‐cone array is particularly advantageous in overcoming the limit given by the incident angle. [ 51,52,53 ] As shown in Figure 3b,c, fluctuation of broadband (400–800 nm) reflectance of the Au/h‐Nanoturf on μ‐cone array with respect to the incident angle of solar spectrum is notably diminished in the case with micro‐cone array (Figure 3c) when compared to flat Au/nanoturf (Figure 3b). In addition, the Au/h‐Nanoturf on μ‐cone array exhibited further decreased reflectance over the range of the broadband spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, with such an enlarged interface area (by almost ≈70% upper compared with a flat), some issues can occur, such as probably leading to more surface recombination . Recently, Zhong et al reported silicon nanopyramids (SiNPs) with lower carrier recombination and thus superior electrical performance (Figure ), probably showing the potential for application in perovskite/silicon TSCs.…”
Section: Light Trapping Structurementioning
confidence: 99%
“…45° tilted‐view SEM image of the a) conventional SiMPs texture and b) SiNPs texture. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Light Trapping Structurementioning
confidence: 99%